Holding the Tensions: Theorising Mediated Publicness in Curriculum-Making - Maglaperidze, Nika; Salokangas, Maija (Philosophical Inquiry in Education, 2026)
This paper poses the question of under what conditions curriculum-making becomes public. The existing literature theorises curriculum-making’s publicness but in a way that leaves the concrete question as to how conditions and orientations for publicness converge unanswered. For instance, Hopmann and Westbury point to institutional underpinnings yet they still remain agnostic as to what orientates schools towards public rather than sectional purposes; Biesta, while recognising the tensions, doesn't provide an account of what institutional conditions would sustain it. In this paper, we propose the concept of mediated publicness: a precarious institutional mode of collective responsibility for basic education. The conditions for mediated publicness are made up of three components: withdrawal of resources from sectional circuits, structural responsibility grounded in intergenerational asymmetry, and professional mediation answerable to collective frameworks. Based on this account, publicness, following from Schleiermacherian dialectics, is shaped through antinomies that must be institutionally sustained rather than resolved. Finally, we draw on the Finnish case to show publicness emerging under a concrete conjuncture, and commodification dismantling it by collapsing said tensions rather than opposing publicness frontally.